2018
DOI: 10.1111/ijfs.13828
|View full text |Cite
|
Sign up to set email alerts
|

Control of lactic acid bacteria in fermented beverages using lysozyme and nisin: test of traditional beverage boza as a model food system

Abstract: Summary The objective of this study was to increase quality and limited shelf‐life of boza (3–15 days), a traditional Balkan origin fermented beverage using lysozyme (LYS) and/or nisin (NIS). For this purpose, the effectiveness of NIS, LYS and LYS:NIS combinations was first tested in a broth medium at 4 °C for 3 weeks on Lactobacillus plantarum, one of the frequently isolated lactic acid bacteria in boza. Stability of LYS and NIS in boza, their effects on LAB counts, and chemical and sensory properties of boza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…lactis, or with LYS, an antimicrobial enzyme obtained from hen egg white, has been applied to inhibit critical food pathogens in fresh or minimally processed fruits, fresh meat, fish products, deli foods, cheeses and whole eggs (Duan et al, 2007, Cé, Noreña, & Brandelli, 2012Duran et al, 2016;Guo et al, 2014;Mehyar, Al Nabulsi, Saleh, Olaimat, & Holley, 2018;Thumula, 2006;Ye, Neetoo, & Chen, 2008a;Ye, Neetoo, & Chen, 2008b;Yuceer & Caner, 2014). The addition of LYS-NIS mixture into different food has also attracted a particular interest since these biopreservatives can show synergetic antimicrobial action on different Gram-positive bacteria including L. monocytogenes (Bhatia & Bharti, 2015;Chung & Hancock, 2000;Gill & Holley, 2000;Mangalassary, Han, Rieck, Acton, & Dawson, 2008;Sozbilen, Korel, & Yemenicioğlu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…lactis, or with LYS, an antimicrobial enzyme obtained from hen egg white, has been applied to inhibit critical food pathogens in fresh or minimally processed fruits, fresh meat, fish products, deli foods, cheeses and whole eggs (Duan et al, 2007, Cé, Noreña, & Brandelli, 2012Duran et al, 2016;Guo et al, 2014;Mehyar, Al Nabulsi, Saleh, Olaimat, & Holley, 2018;Thumula, 2006;Ye, Neetoo, & Chen, 2008a;Ye, Neetoo, & Chen, 2008b;Yuceer & Caner, 2014). The addition of LYS-NIS mixture into different food has also attracted a particular interest since these biopreservatives can show synergetic antimicrobial action on different Gram-positive bacteria including L. monocytogenes (Bhatia & Bharti, 2015;Chung & Hancock, 2000;Gill & Holley, 2000;Mangalassary, Han, Rieck, Acton, & Dawson, 2008;Sozbilen, Korel, & Yemenicioğlu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Samples were collected; 10 g of each sample was diluted in sterile bags with peptone water (0.2% tween‐20) in a stomacher, and serial dilutions were sown in MRS media and incubated at 35 ± 2°C for 48 hr. We used similar preparations without inoculums as negative controls and 0.1% nisin (Danisco, DuPont, Copenhague, Danemark) as a positive control according to what has been previously described for nisin as an efficient growth controller against LAB (Chung & Hancock, 2000; Gedarawatte et al., 2021; Sozbilen et al., 2018; Zhang et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Lysozyme is a good preservative for beverages prolongs the storage period of beverage products. Sozbilen et al [16] showed that the synergistic treatment of lysozyme and Nisin could effectively control the growth of acid-producing bacteria in fermented beverage, without affecting its unique aroma and flavor, and prolonging the shelf life of the product.…”
Section: Application In Liquor and Beveragesmentioning
confidence: 99%